Causes and outcomes of traumatic brain injuries in Uganda: analysis from a pilot hospital registry. Issue 1 (22nd February 2019) - Zia, Nukhba; Mehmood, Amber; Namaganda, Rukia H; Ssenyonjo, Hussein; Kobusingye, Olive; Hyder, Adnan A
Abstract : Background: Traumatic brain injury (TBI) is an important cause of morbidity and mortality in low/middle-income countries. The objective was to assess causes and outcomes of unintentional and intentional TBI among patients presenting to a tertiary care hospital in Uganda. Methods: This study was conducted at Mulago National Referral Hospital, Kampala, Uganda, for 15 months in 2016–2017. Patients of all ages, males and females, presenting to the emergency department with suspected or documented TBI were enrolled. Patient demographics, TBI causes and outcomes were recorded. The outcome of interest was unintentional and intentional TBI. Results: Intent was known for 3749 patients, of these 69.7% were unintentional TBI and 30.3% were intentional TBI. The average age of patients in both groups was similar (28±14 years) with over 70% of patients between 19 and 45 years age group. About 80% were males in both groups. The main causes of unintentional TBI were road traffic injuries (RTI) (88.9%) and falls (11.1%). Pedestrians (42.1%) and motorcycle drivers (28.1%) were the most common road users. Among patients with unintentional TBI, about 43.6% were admitted, 34.0% were sent home. There were 73 deaths: 63 were patients with RTI and 10 had a fall. Although assault (97.1%) was the main cause of intentional TBI, those patients with self-harm were likely to be in severe Glasgow Coma Scale range (39.4%) compared with victims of assault (14.2%). Among patients with intentional TBI, 42.6% were admitted and 37.1% were sent home. There were 30 deaths: 29 were assault victims and 1 of self-harm. Discussion: Unintentional TBI caused by RTI and intentional TBI caused by assault are common among young males attending Mulago Hospital in Kampala. Level of evidence: Prospective observational study, level III.